Citrus. 3 : secret love affair with sister. 3 - Saburouta (Manga author); Fay, Shannon (Seven Seas Entertainment, LLC, 2015)
When her childhood friend Matsuri reenters Yuzu's life, she will stop at nothing to break up Yuzu and Mei's relationship.